DESENVOLVIMENTO SÓCIO-ESPACIAL E DINÂMICA URBANA DA ZONA SUL DA CIDADE DE UBERLÂNDIA - Silva, Kátia Nunes da; Filho, Vitor Ribeiro (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2012)
The urban growth of cities, as well as the cities that reflect serious social problems, especially for loww-incolume population. Thus, the present study promoted a study of urban sprawl in the city of Uberlandia with a focus on understanding the dynamics of urban development established in the southern city,because of intense socioeconomic differentiation which is that region. In this sense, it was essential to accomplish the characterization of the emergence and evolution of urban development in the south, considering the presence of the contradictory y process of social inequality established in the region, to  identify problems in the city from this process.